As unidades de informação dos Institutos Federais no apoio ao desenvolvimento da ciência e da tecnologia: um estudo de percepção sociocognitiva com o uso do protocolo verbal em grupo - Santos, Cintia Almeida da Silva (Universidade Federal de São Carlos, 2012)
The units of information can be considered the repository of knowledge to their institutions as they appease the right to access information along with documentary record. By assisting the development of the Research and Extension activities at Federal Institutes of Education, Science and Technology, this research aimed the investigation and propagation of the importance of a unit of information in the Science and Technology strengthening. The chosen methodology for the theoretical and applied research was qualitative. Its approach was sociocognitive and implemented through questionnaires as well as the realization of the Group Verbal Protocol. Three units of information from the Federal Institute of São Paulo (IFSP) were analyzed, that is, the campuses of São Paulo itself, Garulhos and Salto. The chosen methods were: the realization of a bibliographical survey as theoretical support; the realization of a survey concerning the campuses and their respective units of information; the application of questionnaires and the use of the Group Verbal Protocol technique through the involvement of its participants, that is, management, professors, students, librarians and institutional partners from each campus. Some. The result, achieved through the application of questionnaires, was the socio-historical organizational characterization of the units of information from the IFSP. Some results achieved through the application of the Group Verbal Protocol were the following: the IFSP libraries have primary infrastructure and are still at an early stage. They require systemic structuring; the IFSP libraries do not support the Research and Extension activities which are developed in their campuses; the inexistence of projects derived from the units of information of the various areas in the Research and Extension field; the lack of exchange and partnership among the units of information themselves and other IFSP departments. The findings of the achieved results show the necessity of a greater autonomy, notoriety, visibility and institutional awareness about the importance of the units of information in the socio-educational context of the IFSP. The growth and development of Science and Technology are a pretension and part of the IFSP policy. Therefore, the units of information could spur this growth by truly acting as a repository of scientific, technological and social knowledge.
Keywords: Desenvolvimento social - ciência, tecnologia e sociedade; Educação profissional e tecnológica; Instituto Federal de Educação, Ciência e Tecnologia de São Paulo; Unidades de informação; Protocolos verbais. Ciência, Tecnologia e Sociedade; Institutos Federais; Protocolo Verbal em Grupo; Science, Technology and Society; Professional and Technological Education; Federal Institutes; Units of Information; Group Verbal Protocol; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO